A novel phase-controlling-sintering route for improvement of diopside-based microwave dielectric materials. (July 2015) - Feng, Kuei-Chih; Chou, Chen-Chia; Tsao, Chung-Ya; Chu, Li-Wen; Raevski, Igor P.; Chen, Haydn
Abstract: The present work suggests a new reactive route for obtaining MgTiO3 -doped CaMgSi2 O6 glass–ceramic microwave dielectric material with very low dielectric constant ( ε r ), high quality factors ( Q × f ) and nearly zero temperature coefficient of resonant frequency ( τ f ). Sintering of the mixture of CaMgSi2 O6 glass and synthesized MgTiO3 powders at 950 °C results in glass-ceramics containing Mg2 SiO4 and CaTiO3 phases. Such glass-ceramics possess increased quality factors and improved temperature coefficient of resonant frequency, because the Mg2 SiO4 and CaTiO3 phases own ultra-high Q × f and positive τ f, respectively. Microstructure features and EPMA line scan show the concentration gradients of Ca, and Si atoms altering from matrix region toward MgTiO3 particle. These data indicate that during the liquid phase sintering silica glass reacts with MgTiO3 ceramic particles forming the Mg2 SiO4 and CaTiO3 phases.